Characteristics and expectations among emergency department patients in India. - Kevin Davey; Sumin Jacob; Nilesh Prasad; Manjula Shri; Richard Amdur; Janice Blanchard; Jeffrey Smith; Katherine Douglass (Public Library of Science (PLoS), 2022)
In India, and many low-middle income countries (LMICs), emergency medicine (EM) remains a poorly defined specialty and an unregulated field of clinical practice. Recognition of the attitudes, understanding, and expectations of patients presenting to Indian EDs will be crucial to the continued development of EM as a specialty. This is a multicenter, prospective, cross sectional study of adult and pediatric patients presenting to the ED in three geographically distinct regions of India. Participants were surveyed about their expectations regarding the type of care that they expected to receive, previous treatment options they have utilized, basic understanding of ED operations, factors contributing to their decision to seek ED care, and basic demographic information. 779 patients were approached to participate in the study, of which 698 (90%) completed the survey. Common ways that patients reported learning about the ED were referral from another healthcare provider (45%) and recommendation by a family member (61%). Participants chose the ED was because they thought they would be seen quickly (89%), would receive acute pain management (45%), their regular outpatient care was closed (45%), or were sent by another doctor (45%). Patients expected to wait 0.3 hours (18 minutes) on average to see a doctor in the ED. Over 75% or patients expected to see a specialist consultant in the ED and 12% expected to see their personal physician. Eighty-five percent of patients were triaged as moderate or high acuity, and 74% of patients were admitted. This study found that ED in India is utilized by a population with an extremely high acuity of medical illness that attempts to access healthcare through multiple avenues. Patients most frequently visit the ED due to a referral from another healthcare provider or family member. Most patients are aware of the existence of the ED, though understanding of available services may be lacking. Future research should focus on community outreach and education initiatives on ED services.